Self-limited monolayer graphene growth on SiC with propane-hydrogen CVD - Chiara Mastropasqua; Ahmed El Alouani; Matthieu Paillet; Marc Portail; Mathieu Koudia; Mathieu Abel; Yvon Cordier; Benoît Jouault; Isabelle Berbezier; Sandrine Juillaguet; Adrien Michon (npj 2D Materials and Applications)
Abstract Among the different methods to grow graphene on silicon carbide (SiC), the chemical vapor deposition (CVD) in a hydrogen atmosphere has several interesting features arising from the use of this gas. Despite its versatility and its ability to grow graphene with a quality allowing applications in electrical metrology, this synthesis method remains largely understudied. This work is specifically dedicated to this growth technique in conditions leading to the epitaxy of graphene on a buffer layer. We first show that hydrogen has several effects during the cooling down, possibly leading to hydrogen intercalation beneath graphene, or even to graphene etching. Then, we use a specific cooling under argon, allowing the suppression of hydrogen effects, to follow the successive phases of the graphene formation, from the nucleation of islands and ribbons to their coalescence on SiC. Finally, we demonstrate that graphene growth is, in our growth conditions, self-limited to a unique monolayer.